Haptic Choice Blindness. (May 2013) - Steenfeldt-Kristensen, Catherine; Thornton, Ian M.
Choice blindness is the failure to notice a mismatch between intention and outcome when making decisions. It is unknown whether choice blindness occurs when participants have extended interaction with real objects. Here, we examined the case when objects could be touched but not seen. Participants examined pairs of common, everyday objects inside a specially constructed box where a silent turntable was used to switch objects between initial choice and later justification. For similar pairs of objects, we found detection rates of around 22%, consistent with previous studies of choice blindness. For pairs consisting of more distinctive exemplars, the detection rate rose to 70%. Our results indicate that choice blindness does occur after haptic interaction with real objects, but is strongly modulated by similarity.